Effect of chemical disinfection on the dimensional stability of polyvinyl ether siloxane impression material: a systemic review and meta-analysis - Saeed Awod Bin Hassan; Abdulkhaliq Ali F Alshadidi; Lujain Ibrahim N Aldosari; Artak Heboyan; Ravinder S Saini (BMC, 2023)
Abstract Background and objectives Polyvinyl ether siloxane (PVES) possesses ideal characteristics for making precise and accurate dental impressions. PVES dimensional stability owes to its better polymeric properties derived from its parent materials poly ethers and polyvinyl siloxanes. As recommended use of chemical disinfecting agents is getting more popular, there is a growing concern associated with the effect of disinfectants on PVES dimensional stability. This study was aimed to understand the PVES behavior when subjected to chemical disinfectants. Materials and methodology The data was collected from research studies retrieved from Google Scholar, Scopus, and PubMed using MeSH terms of keywords "vinyl polyether siloxane AND Disinfection" or (Vinyl polyether siloxane OR polyvinyl siloxane ether OR PVES) AND (disinfectant OR disinfection)" without any restriction to publication date. The PRISMA (Preferred Reporting Items for Systemic Review and Meta-Analysis) directions were observed during the data collection, screening of studies, and meta-analysis. The primary data were retrieved, and batch exported from databases using Harzing's Publish or Perish software; primary analysis was performed in Microsoft Excel, while statistical analysis for effect size, two-tailed p-values, and heterogeneity among studies was performed using Meta Essentials. The effect size was calculated using Hedge's g values at the 95% confidence level using the random-effects model. Heterogeneity among studies was measured using the Cochrane Q and I2. Results and conclusion Dental impressions made from the PVES elastomeric impression materials showed no significant changes in dimensional stability. Immersion in the chemical disinfectant for 10 min was associated with clinically irrelevant changes in the dimensions of the PVES impressions. Disinfection with sodium hypochlorite was associated with clinically significant changes in dimensions, with a two-tailed p-value of 0.049. Disinfection with 2-2.5% glutaraldehyde solution was not associated with any significant dimensional variability.